Recursos Familiares e o Desempenho Cognitivo dos Alunos do Ensino Básico Brasileiro - José Francisco Soares; Ana Cristina Murta Collares (Universidade do Estado do Rio de Janeiro, 2006)
This article discusses the processes by which family structure affects students´ cognitive performance in Brazilian schools. The article´s basic premise is that family influence is not a uni-dimensional construct, and the study thus uses four dimensions to capture such influence. The effects of these factors on students' performance are measured through a school attainment analysis model. The data are compatible with a model in which the parents´ involvement acts as a mediating factor for the action of cultural resources, which in turn depend on economic resources, which have only indirect effects on students´ cognitive performance in primary school.